2017
DOI: 10.1210/er.2016-1105
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism Abnormalities in Cushing Syndrome: From Molecular Basis to Clinical Management

Abstract: An impaired glucose metabolism, which often leads to the onset of diabetes mellitus (DM), is a common complication of chronic exposure to exogenous and endogenous glucocorticoid (GC) excess and plays an important part in contributing to morbidity and mortality in patients with Cushing syndrome (CS). This article reviews the pathogenesis, epidemiology, diagnosis, and management of changes in glucose metabolism associated with hypercortisolism, addressing both the pathophysiological aspects and the clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 344 publications
0
92
1
1
Order By: Relevance
“…Our results also suggest OGTTs should be interpreted carefully in patients with diabetes secondary to glucocorticoid therapy or with endogenous cortisol disorders, with special attention to the transient post-OGTT dynamics. This is important in view of the fact that an OGTT may not be performed when a patient’s fasting glucose is normal, thus leading to an underestimation of the prevalence of diabetes in hypercortisolism ( 15 ). Our model is also a step towards an integrated theoretical framework that accounts for the circadian dynamics of insulin and glucose utilisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results also suggest OGTTs should be interpreted carefully in patients with diabetes secondary to glucocorticoid therapy or with endogenous cortisol disorders, with special attention to the transient post-OGTT dynamics. This is important in view of the fact that an OGTT may not be performed when a patient’s fasting glucose is normal, thus leading to an underestimation of the prevalence of diabetes in hypercortisolism ( 15 ). Our model is also a step towards an integrated theoretical framework that accounts for the circadian dynamics of insulin and glucose utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…GLUTs are also involved in glucose sensing in pancreatic beta cells, with the caveat that the GLUT isoforms present in these insulin-secreting cells possess a different glucose sensitivity threshold than those in fat and muscle cells ( 28-31 ). Furthermore, CORT regulates glucose uptake by antagonising the insulin-mediated translocation of GLUTs in fat and muscle ( 32-35 ), by modulating insulin secretion in pancreatic beta cells ( 36-39 ), and by stimulating liver gluconeogenesis and glycogenolysis ( 4, 15 ). Importantly, our model considers the distribution of GLUT isoforms with different glucose affinities for glucose transport across cell membranes (Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al reported that patients with au-tonomous cortisol secretion presented obesity, glucose intolerance, arterial hypertension, and, increased CIMT compared with patients with nonfunctional adrenal adenoma (21). A grater prevalence of diabetes, insulin resistance, dyslipidemia, and increased inflammation was observed in patients with Cushing's syndrome (24,25). Low-grade inflammation participates in an increased cardiovascular risk in patients with Cushing's syndrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid excess affects all major peripheral tissues involved in glucose regulation (20,66). Furthermore, significant overlap exists between these pathways and those leading to visceral adiposity and dyslipidemia.…”
Section: Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%